No genetic causal association between Alzheimer’s disease and osteoporosis: A bidirectional two-sample Mendelian randomization study - Hu, Hongxin; Mei, Jian; Cai, Yuanqing; Ding, Haiqi; Niu, Susheng; Zhang, Wenming; Fang, Xinyu (Frontiers in Aging Neuroscience, 2023)
Objective Many observational studies have found an association between Alzheimer’s disease (AD) and osteoporosis. However, it is unclear whether there is causal genetic between osteoporosis and AD. Methods A two-sample Mendelian randomization (MR) study was used to investigate whether there is a causal relationship between osteoporosis and AD. Genes for osteoporosis and AD were obtained from published the genome-wide association studies (GWAS). Single nucleotide polymorphisms (SNPs) with significant genome-wide differences (p < 5 × 10−8) and independent (r2 < 0.001) were selected, and SNPs with F ≥ 10 were further analyzed. Inverse variance weighted (IVW) was used to assess causality, and the results were reported as odds ratios (ORs). Subsequently, heterogeneity was tested using Cochran’s Q test, pleiotropy was tested using the MR–Egger intercept, and leave-one-out sensitivity analysis was performed to assess the robustness of the results. Results Using the IVW method, MR Egger method, and median-weighted method, we found that the results showed no significant causal effect of osteoporosis at different sites and at different ages on AD, regardless of the removal of potentially pleiotropic SNPs. The results were similar for the opposite direction of causality. These results were confirmed to be reliable and stable by sensitivity analysis. Conclusion This study found that there is no bidirectional causal relationship between osteoporosis and AD. However, they share similar pathogenesis and pathways.